2023
DOI: 10.1177/02676583231169127
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orthography in Mandarin speakers’ production of English voiceless stops

Abstract: This article provides a review of previous studies that have examined the effects of orthography on establishing contrastive phonological representations in second language acquisition and presents results from an original study on Mandarin speakers’ production of English stops investigating how the presence of orthography affects the production of phonological categories that involve allophony. English voiceless stops are canonically represented as aspirated [ph, th, kh] in word-initial/stressed onset positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…The studies in this section indicate that distinct script input can support the lexical encoding (Hao and Yang 2021) and the perception and production of nonnative contrasts (Mok et al 2018), as well as the spoken word recognition of rule-governed phonological variants (Han and Kim 2022). The only study to indicate that distinct script input had an inhibitory effect for experienced learners was in the context of producing allophones in pseudowords, and this effect did not extend to real words (Lu and Lee 2023). However, it may be the case that the benefits of distinct script inputs are limited by various factors, such as lack of familiarity, systematicity, and perceptibility of the target phonology.…”
Section: Production Ofmentioning
confidence: 91%
See 2 more Smart Citations
“…The studies in this section indicate that distinct script input can support the lexical encoding (Hao and Yang 2021) and the perception and production of nonnative contrasts (Mok et al 2018), as well as the spoken word recognition of rule-governed phonological variants (Han and Kim 2022). The only study to indicate that distinct script input had an inhibitory effect for experienced learners was in the context of producing allophones in pseudowords, and this effect did not extend to real words (Lu and Lee 2023). However, it may be the case that the benefits of distinct script inputs are limited by various factors, such as lack of familiarity, systematicity, and perceptibility of the target phonology.…”
Section: Production Ofmentioning
confidence: 91%
“…Several studies have also looked at cross-scriptal orthographic effects on L2 allophonic variation. Lu and Lee (2023) conducted an imitation production task with experienced L1 Mandarin learners of L2 English. They found that the accurate production of allophonic unaspirated stops was impeded by exposure to distinct Roman script input, in comparison to audio-only imitation.…”
Section: Experienced Learnersmentioning
confidence: 99%
See 1 more Smart Citation